2019
DOI: 10.1038/s41598-019-49595-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ag@Co-Al Layered Double Hydroxides Reinforced poly(o-phenylenediamine) Nanohybrid for Efficient Electrochemical Detection of 4-Nitrophenol, 2,4-Dinitrophenol and Uric acid at Nano Molar Level

Abstract: In this paper, Co-Al layered double hydroxides (LDHs), Co-Al LDHs/poly(o-phenylenediamine) (PoPD) and Ag nanoparticles decorated Co-Al LDHs/PoPD (Ag@Co-Al LDH/PoPD) samples were prepared. The as-prepared samples were characterized by XRD, Raman, XPS, FT-IR, DRS-UV-Vis, PL and TGA techniques. The salient features of morphology and size of the samples were determined using FESEM, and HR-TEM. Then, the samples were coated on glassy carbon electrode (GCE) and employed for sensing of 4-nitrophenol (4-NP), 2,4-dinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 57 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…Furthermore, the Ni based nanocomposite, MgFe 2 O 4 NPs proved to be a good electrocatalyst for 4nanoparticles (NPs) reduction (Baby et al, 2019;Mejri et al, 2019). Carbon nanotubes decorated with metals like Pt, Pd, Ag, monometallic-Au, and bimetallic-Au show excellent electrocatalytic activity toward nitrophenols (Liu et al, 2015;Umar et al, 2016;Sun et al, 2017;Dhanasekaran et al, 2019;Ding et al, 2019), but their low earth abundance and high cost inhibits their practical applicability. In order to address these issues researchers have proposed alternative approaches including replacing the precious metals with non-noble metals or producing metal free systems with high stability and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Ni based nanocomposite, MgFe 2 O 4 NPs proved to be a good electrocatalyst for 4nanoparticles (NPs) reduction (Baby et al, 2019;Mejri et al, 2019). Carbon nanotubes decorated with metals like Pt, Pd, Ag, monometallic-Au, and bimetallic-Au show excellent electrocatalytic activity toward nitrophenols (Liu et al, 2015;Umar et al, 2016;Sun et al, 2017;Dhanasekaran et al, 2019;Ding et al, 2019), but their low earth abundance and high cost inhibits their practical applicability. In order to address these issues researchers have proposed alternative approaches including replacing the precious metals with non-noble metals or producing metal free systems with high stability and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report where Ag was immobi- was shown to reduce 4-NP at a low potential (À 0.3 V vs SCE) in aqueous buffer environment. [9] Liguang et al also reported a highly recyclable hybrid material, xCu-LDH/rGO, which catalyses NaBH 4 mediated 4-NP reduction. [60] Haiqing et al reported a Pd/ CNT composite as highly efficient catalyst.…”
Section: Electrochemical Reduction Of 4-np On Ldh Catalystsmentioning
confidence: 99%
“…LDHs often exhibit a huge surface area and pore volume, which enables them to be used in surface catalysis [7] . Currently, LDHs are widely explored in several applications such as anion exchange, [8] electrochemical sensors [9] and as catalysts in water treatment [10] . The constant increase in the number of toxic organic compounds in the environment, mainly from pharmaceutical and pigments industry has raised a lot of attention over the years.…”
Section: Introductionmentioning
confidence: 99%
“…4-NP (p-nitrophenol; P-NP or 4-NP) is one kind of severely toxic or explosive compound with substituted phenols. 14 Many of the environmental councils recommend the water quality parameters be set to a maximum level concentration of 4-NP in drinking water. The United States Environmental Protection Agency (US EPA) has permitted the limit of 4-NP in drinking water at 60 ppb (∼0.43 μM), the European Commission suggested that the maximum limit be 0.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 4-NP induces methemoglobin formation, which is harmful and damages the central nervous system, liver, kidney, and blood because of its prospective carcinogenicity and mutagenicity at trace levels. 14 Among them, removing 4-NP from wastewater is an important and urgent environmental issue. Thus, the electrochemical approches are prefered to avoid expensive instrumentation, time-consuming progression, nonspecificity, and pretreatment for real-life samples and the traditional mark analytical methods like chromatography, spectrophotometry, HPLC, polarography, and capillary zone electrophoresis.…”
Section: Introductionmentioning
confidence: 99%